Recurrence pattern and prognostic factors for survival in cervical cancer with lymph node metastasis. Issue 6 (25th March 2021) - Kilic, Cigdem; Kimyon Comert, Gunsu; Cakir, Caner; Yuksel, Dilek; Codal, Bahadır; Kilic, Fatih; Turkmen, Osman; Karalok, Alper; Moraloglu Tekin, Ozlem; Boran, Nurettin; Turan, Taner
Abstract: Aim: The aim of this study is to evaluate the recurrence pattern and oncological outcomes in cervical cancer (CC) patients with lymph node metastasis. Methods: This study included 224 International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB1‐IIIB CC patients with pathologically proven lymph node metastasis. Surgical intervention was grouped as hysterectomy performed/not performed. Adjuvant therapy decision was made by the tumor board. Radiotherapy was applied to all patients with lymph node metastasis. Results: Only paraaortic lymph node metastasis was determined as an independent prognostic factor for recurrence. Presence of paraaortic lymph node metastasis increased the risk of recurrence more than two times (odds ratio: 2.129; 95% confidence interval: 1.011–4.485; p = 0.047). An independent prognostic factor for death because of disease was age only. Risk of death was nearly doubled with younger age (odds ratio: 2.693; 95% confidence interval: 1.064–6.184; p = 0.037). Conclusion: The most of recurrences were located at distant sites and multiple regions. Paraaortic lymph node metastasis was the only independent prognostic factor for recurrence, in spite of that age was an independent predictor for risk of death in patients with early stage or locally advanced CC and also with surgically proven metastatic lymph nodes. Furthermore, the presence of the paraaortic lymph node metastasis was significantly associated with distant recurrence. Therefore, more appropriate and individualized therapy strategy focusing on intenser systemic chemotherapy options in addition to radiotherapy should be taken into consideration according to paraaortic lymph node metastasis and age.